THE INFLUENCE OF AUTHORITARIAN LEADERSHIP AND MARKET CULTURE ON JOB HOPPING DECISION AMONG GENERATION Z EMPLOYEES, WITH CAREER ADAPTABILITY AS A MEDIATING VARIABLE, IN THE HOSPITALITY INDUSTRY OF YOGYAKARTA SPECIAL REGION - Ardian Priambudi; Maria Pampa Kumalaningrum; Shita Lusi Wardhani (Faculty of Economics and Business, Universitas Warmadewa, 2026)
The hospitality industry in the Special Region of Yogyakarta faces the challenge of high job hopping intentions among generation Z employees. This study aims to examine the influence of authoritarian leadership and target-oriented organizational culture (market culture) on job hopping decision, with career adaptability as a mediating variable. Data were collected from 160 respondents consisting of Gen Z employees working in hospitality sector companies. The analysis was conducted using a quantitative approach with the SEM-PLS method. The findings indicate that authoritarian leadership and market culture have a significant positive effect on job hopping. Career adaptability was found to mediate this relationship, meaning that the higher an individual’s career adaptability, the greater their tendency to respond to work pressures by changing jobs. The implications of these findings highlight the importance of managing leadership styles and adjusting organizational culture to align with the characteristics of generation Z in order to reduce job hopping tendencies in the hospitality industry.